Effects of Planting Geometry and Fertilizer Management on Light Interception, Chlorophyll Content and Productivity in Baby Corn Cultivation - Kakon, SS; Chowdhury, JA; Ali, MZ; Karim, MR; Chowdhury, DA (Bangladesh Agronomy Journal, 2023)
A field experiment was conducted during during rabi seasons (December to March) of 2019-20 and 2020-21 to find out optimum plant spacing and fertilizer levels on yield of baby corn. Three plant spacing viz, S1=40 cm × 20 cm (1,25000 plants ha−1), S2=50 cm × 20 cm (100000 plants ha−1) and S3 =60 cm × 20 cm (83333 plants ha−1) and three fertilizer doses viz, F1 = 150- 30- 50- 25-3. 5- 1.5 kg ha−1of NPKSZnB (Recommended fertilizer dose for baby corn), F2 = F1 + 25% NPK and F3 = F1 + 50% NPK, were used as treatments. Results revealed that, planting geometry and fertilizer levels showed great influence on leaf area index (LAI), light interception, dry matter production and yield of babycorn. LAI was found the highest with the population of 125000 plants ha−1 receiving N225 P45 K75 kg ha−1.Light absorption was maximum at densely plant population with N225P45K75 kg ha−1. Response of soil-plant-analysis development (SPAD) value to planting geometry and fertilizer level was found significant. Plants grown with 40 cm × 20 cm spacing (125000 plants ha−1) with recommended ferltilizer dose + 50% N- P- K of RF gave the highest dehusked cob yield over the years (3.42 and 3.73 t ha–1) which was followed by 40cm × 20 cm (1,25,000 plants ha−1) with recommended fertilizer dose + 25% N-P-K of RF. Though S1F3 combination gave the highest gross return (Tk.333140 ha–1 in 2019-20 and Tk. 378900 ha–1 in 2020-21) but the highest benefit cost ratio over the years (3.64 and 3.83) was recorded in S1F2 treatment. The overall results indicated that 40 cm × 20 cm (1,25,000 plants ha−1) with fertilizer dose of RFD + 25% NPK (N187.5 P37.5K62.5 S25Zn3. 5B1.5 kg ha−1) might be economically profitable for baby corn production. Bangladesh Agron. J. 2023, 26(1): 96-103